The Issue of Eviction and the Related Problems of Social Housing in the Polish Legal System - Dziewa, Róża (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2015)
The aim of the study is to evaluate the eviction and social housing in the Polish legal system. Presenting the selected topic the author focus on the functioning of the eviction and social housing as well as on the Report by the Polish Supreme Chamber of Control in order to prove the deteriorating of the eviction.